PESQUISA DE PARASITOS EM ALFACE E COUVE PROVENIENTES DE FEIRAS DA REGIÃO CENTRAL E SUAS MEDIAÇÕES NA CIDADE DE ANÁPOLIS-GO - Léa Resende Moura; Thiago Santos; Ângela Alves Viegas (UniEVANGÉLICA, 2015)
Objective: To evaluate the parasitological quality of vegetables lettuce (Lactuca sativa) and cabbage (Brassica oleracea) marketed by 28 stalls divided into four exhibitions located in central and mediations in the city of Anápolis-GO. Methods: A total of 28 samples of lettuce and 28 samples of cabbage by spontaneous sedimentation techniques and Craig. Results: We obtained 16% contamination by intestinal parasites in 56 samples. Lettuce showed greater contamination (25%) and cabbage showed contamination of 7.1%. The enteroparasite more prevalent among the lettuce was Entamoeba coli (17.8%); on cabbage samples, as well as Entamoeba coli (3.5%), we found Ascaris lumbricoides (3.5%). Conclusions: Probably the presence of these enteroparasito can be related to a low hygienic standard in some management steps of greenery. There is a clear need to increase health education of vegetable handlers and improving the quality of water used in these vegetable crops processes.